Evaluation of 4 Multisection CT Systems in Postoperative Imaging of a Cochlear Implant: A Human Cadaver and Phantom Study - Verbist, B.M.; Joemai, R.M.S.; Teeuwisse, W.M.; Veldkamp, W.J.H.; Geleijns, J.; Frijns, J.H.M. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Postoperative imaging of cochlear implants (CIs) needs to provide detailed information on localization of the electrode array. We evaluated visualization of a HiFocus1J array and accuracy of measurements of electrode positions for acquisitions with 64-section CT scanners of 4 major CT systems (Toshiba Aquilion-64, Philips Brilliance-64, GE LightSpeed-64, and Siemens Sensation-64).MATERIALS AND METHODS: An implanted human cadaver temporal bone, a polymethylmethacrylate (PMMA) phantom containing a CI, and a point spread function (PSF) phantom were scanned. In the human cadaver temporal bone, the visibility of cochlear structures and electrode array were assessed by using a visual analog scale (VAS). Statistical analysis was performed with a paired 2-tailed Student t test with significant level set to .008 after Bonferroni correction. Distinction of individual electrode contacts was quantitatively evaluated. Quantitative assessment of electrode contact positions was achieved with the PMMA phantom by measurement of the displacement. In addition, PSF was measured to evaluate spatial resolution performance of the CT scanners.RESULTS: VAS scores were significantly lower for Brilliance-64 and LightSpeed-64 compared with Aquilion-64 and Sensation-64. Displacement of electrode contacts ranged from 0.05 to 0.14 mm on Aquilion-64, 0.07 to 0.16 mm on Brilliance-64, 0.07 to 0.61 mm on LightSpeed-64, and 0.03 to 0.13 mm on Sensation-64. PSF measurements show an in-plane and longitudinal resolution varying from 0.48 to 0.68 mm and 0.70 to 0.98 mm, respectively, over the 4 scanners.CONCLUSION: According to PSF results, electrode contacts of the studied CI can be visualized separately on all of the studied scanners unless curvature causes intercontact spacing narrowing. Assessment of visibility of CI and electrode contact positions, however, varies between scanners.